The impact of IT capability and organizational learning on halal food SMEs' performance - Liliana Inggrit Wijaya; Bobby Ardiansyahmiraja; Adhika Putra Wicaksono; Andri Rianawati; Faizal Susilo Hadi; Marwin Antonius Rejeki Silalahi; Muhammad Izharuddin; Zunairoh (Cogent Business & Management, 2023)
Halal food is an especially important sector in many developing countries. Many of the halal food in those countries are supplied by SMEs. Although the importance of this sector is certain, studies investigating the organizational aspect of halal food SMEs are still limited. The present study tries to expand the knowledge of organizational behaviour aspects in halal food SMEs since it is crucial in creating the sustainability of halal food SMEs. The present study uses partial least square structural equation modelling (PLS-SEM). The questions used to measure the variables used in this study were developed by adopting previous studies' instruments. This research discovered the importance of IT capability and organizational learning on organizational performance. IT capability, Knowledge transfer effectiveness, and Absorptive capacity are found to have a significant relationship with organizational performance measured by Balanced Scorecard (BSC). Furthermore, the effect of IT capability and Knowledge transfer effectiveness are not only direct but also mediated by Absorptive capacity. From the findings, there are key implications. First, by utilizing digital capabilities in their business processes, SMEs can more easily obtain new knowledge. Second, when SMEs learn new things from digitalization, they can associate their knowledge with new information. Third, the ability to use technology helps human resources in SMEs to increase knowledge, thus encouraging SMEs to create innovation and business competitiveness. This ultimately has an impact on increasing sales and cost-effectiveness.
Keywords: 650; absorptive capacity; IT capability; knowledge transfer effectiveness; organizational learning; organizational performance; Smes